A human brainstem glioma xenograft model enabled for bioluminescence imaging - Hashizume, Rintaro; Ozawa, Tomoko; Dinca, Eduard B.; Banerjee, Anuradha; Prados, Michael D.; James, Charles D.; Gupta, Nalin (Journal of neuro-oncology, 2010)
Despite the use of radiation and chemotherapy, the prognosis for children with diffuse brainstem gliomas is extremely poor. There is a need for relevant brainstem tumor models that can be used to test new therapeutic agents and delivery systems in pre-clinical studies. We report the development of a brainstem-tumor model in rats and the application of bioluminescence imaging (BLI) for monitoring tumor growth and response to therapy as part of this model. Luciferase-modified human glioblastoma cells from five different tumor cell sources (either cell lines or serially-passaged xenografts) were implanted into the pontine tegmentum of athymic rats using an implantable guide-screw system. Tumor growth was monitored by BLI and tumor volume was calculated by three-dimensional measurements from serial histopathologic sections. To evaluate if this model would allow detection of therapeutic response, rats bearing brainstem U-87 MG or GS2 glioblastoma xenografts were treated with the DNA methylating agent temozolomide (TMZ). For each of the tumor cell sources tested, BLI monitoring revealed progressive tumor growth in all animals, and symptoms caused by tumor burden were evident 26–29 days after implantation of U-87 MG, U-251 MG, GBM6, and GBM14 cells, and 37–47 days after implantation of GS2 cells. Histopathologic analysis revealed tumor growth within the pons in all rats and BLI correlated quantitatively with tumor volume. Variable infiltration was evident among the different tumors, with GS2 tumor cells exhibiting the greatest degree of infiltration. TMZ treatment groups were included for experiments involving U-87 MG and GS2 cells, and in each case TMZ delayed tumor growth, as indicated by BLI monitoring, and significantly extended survival of animal subjects. Our results demonstrate the development of a brainstem tumor model in athymic rats, in which tumor growth and response to therapy can be accurately monitored by BLI. This model is well suited for pre-clinical testing of therapeutics that are being considered for treatment of patients with brainstem tumors.